The influence of promotion and online customer reviews on purchase decisions at Shopee in Bogor City - Furi Indriyani (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the influence of Promotion and Online customer reviews on Purchase Decisions at Shopee in Bogor City. This research is based on quantitative with explanatory method approaches. The sampling technique used non-probability sampling through purposive sampling with 100 respondents. The data analysis technique used multiple regression analysis. Based on the results of multiple linear regression analysis, the Simultaneous test result (F-test) shows that Fcount 87,738> Ftable of 3,090, meaning that Promotion and Online Costumer Review simultaneously significantly influence Purchase Decision at Shopee in Bogor City. Partial Test Results (t-test) indicate that the variable Promotion (X1) tcount 4,783 > ttable1,661, which means that the Promotion variable partially has a significant influence on Purchase Decision (Y), Online Costumer Review variable (X2) shows tcount 9,007>  ttable1,661. This result shows that Online customer Review partially significantly influences Purchase Decision (Y). From the regression analysis, the coefficient of determination (R²) is obtained to be 0,644 or 64,4%. This value indicates that the contribution of promotion and Online Customer review variables On Purchase Decisions reaches 64,4%.